STING regulates NETs formation by activating GSDMD in influenza viral pneumonia - Huang, Rongrong; Chen, Ranran; Xing, Lijuan; Wu, Lianhao; Zhu, Wenwen; Jing, Junsong; Zhou, Ting; Wu, Yueguo; Zhang, Sheng; You, Zhenqiang (Frontiers in Immunology, 2025)
BackgroundViral pneumonia is the most common and lethal pandemic disease, but there are no broad-spectrum antiviral drugs with high genetic barriers to resistance. To elucidate the mechanisms of viral pneumonia progression and potential targets for its treatment.MethodsViral pneumonia models were induced by the PR8 virus strain in wild-type (WT) and STING knockout (STING-KO) mice. Series of molecular biology techniques were used to evaluate the severity of pneumonia and cytokine levels.ResultsIn this study, STING (stimulator of interferon genes) was activated in the lungs of virus-infected mice, leading to cytokine production and amplification of the immune response, thereby causing rapid deterioration of symptoms. Furthermore, excessive activation of innate immune response via STING was prevented by a STING inhibitor (C-176), which significantly reduced viral lung inflammation. The formation of neutrophil extracellular traps (NETs) was similarly suppressed during viral pneumonia treatment with STING inhibitors (C-176), and NETs formation and STING expression were positively correlated, indicating that STING plays an important role in NETs formation. Symptoms of pneumonia in STING-KO mice infected with PR8 were significantly milder than those in WT mice, and NETs were less likely to form in the lung tissue of STING-KO mice. Additionally, transcriptomic analysis revealed that STING-mediated regulation of NETs may be associated with gasdermin D (GSDMD), and immunoprecipitation experiments revealed that STING, GSDMD, and NETs-related proteins interact with each other. Immunofluorescence assays revealed that in neutrophils from WT mice, STING and GSDMD were colocalized on the membrane after viral infection, whereas in neutrophils from STING-KO mice, GSDMD expression was decreased after exposure to the virus.ConclusionsOur study demonstrated that targeted intervention with STING alleviated pneumonia by inhibiting inflammation and NETs formation. The study also revealed that blocking STING could inhibit the activation of GSDMD to inhibit NETs formation, slowing the progression of viral pneumonia.